Investigations into the development, diagnosis and treatment of oral cancer - O'Callaghan, Katherine (Trinity College (Dublin, Ireland). School of Dental Science, 2015)
Oral cancer is the sixth most common cancer in the world and has one of the highest mortality rates primarily due to the disease being largely asymptomatic until the latter stages. It is among one of the major worldwide public health problems with the incidence and mortality rates rising in several regions of the world, including Europe, South Central Asia and Australia. Smoking poses the highest risk for oral cancer followed closely by the consumption of alcohol. Furthermore diagnosis and treatment of oral cancer can prove to be challenging which seems surprising since the site of malignancy is so easily accessible.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin